Epidemiology of abdominal aortic aneurysms in a Chinese population during introduction of endovascular repair, 1994 to 2013: A retrospective observational study. Issue 9 (March 2018) - Tam, Greta; Chan, Yiu Che; Chong, Ka Chun; Lee, Kam Pui; Cheung, Grace Chung-yan; Cheng, Stephen Wing-keung
Abstract : Abstract: The aim of this study was to examine changes in abdominal aortic aneurysm repair and mortality during a period when endovascular aneurysm repair (EVAR) was introduced. Open repair surgery was the mainstay of treatment for abdominal aortic aneurysm (AAA), but EVAR is increasingly utilized. Studies in the Western population have reported improved short-term or postoperative mortality and shorter length of hospital stay with EVAR. However, scant data are available in the Chinese population. We conducted a retrospective observational study using the database of the Hospital Authority, which provides public health care to most of the Hong Kong population. AAA patients admitted to public hospitals for intact repair or rupture from 1994 to 2013 were included in this study. We calculated the incidence of ruptured AAA, annual repair rates according to type of AAA and surgery, as well as death rates (operative and overall short-term). We calculated whether there were significant changes over time and compared short-term mortality between open surgery and EVAR. One thousand eight hundred eighty-five patients were admitted for intact repair and 1306 patients were admitted for AAA rupture, of whom 795 underwent rupture repair. Intact repair rates significantly increased in all age groups (7.3–37.8%, P  < .001) over the study period. The incidence of ruptured AAA increased, in all age groups, except in < 64 years old. By 2013, 85% of intact repairs and 55.4% of rupture repair were done by EVAR. Over time, there was a significant decrease in operative mortality for intact repair (16.5 in 1994 to 7.1 in 2013, P  = .01) and rupture repair (59.7 in 1994 to 30.8 in 2013, P  = .003). Over the same time period, short-term AAA-related deaths decreased by more than half (73% in 1994 to 24% in 2013, P  < .001), with a significant decline in all age groups, except < 64 years old. Short-term mortality was significantly lower for EVAR than for open repair (17.2% vs 40.3%, P  < .01). Short-term AAA-related deaths have declined likely due to decreased operative mortality and rupture deaths during the period of EVAR introduction and expansion.